Evaluasi Tingkat Kematangan Tata Kelola Teknologi Informasi pada Layanan Informasi Publik dan Pengaduan Masyarakat Pemerintah Kota Kupang menggunakan COBIT 4.0 - Yohanes Payong (Badan Penelitian dan Pengembangan Daerah Kota Kupang, 2020)
The development of Information Technology (IT) has a very significant impact on changes in the current government system. IT implementation in all sectors of government is one solution to improve the interaction of government services to the community (Government to Citizen G to C). For this reason, it is deemed necessary to apply a framework in information technology governance to ensure the application of information technology can be made possible in the government system, maximize all existing benefits, and minimize various risks to IT management properly and appropriately, in addition, it can be used as a resource by government officials responsibly. In order to achieve these objectives, it is necessary to evaluate the planning, implementation process, monitoring actions and continuous evaluation. With the implementation of Smart City, it is necessary to have a continuous evaluation of information technology services at the Kupang City Government. In this study, COBIT 4.0 is used as an IT governance approach to determine the maturity level of IT governance. This study uses six tributes of COBIT 4.0 maturity, using descriptive analysis; each maturity attribute will be evaluated to determine the maturity level of public information services and public complaint services. The results of the evaluation of this study determine two types of conditions, namely: current (as is) and expected (to be). Based on the maturity index of public information services and public complaints, the maturity index in its current state (as is) has a value of 2.0. This index value states that the predicate for maturity is